Will industry influence derail UN summit?. (23rd August 2011) - Cohen, Deborah
Abstract : In the run up to the UN summit on non-communicable diseases, there are fears that industry interests might be trumping evidence based public health interventions. Will anything valuable be agreed? Deborah Cohen reports